PENINGKATAN KETERAMPILAN DISKUSI PADA MATERI CERAMAH MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY - Pakombong, Hendrik (Universitas Wijaya Kusuma Surabaya, 2021)
This study aims to improve the discussion learning process and improve discussion skills of class XI students of SMA Negeri 1 Muara Wahau through the Two Stay Two Stray learning model. The Two Stay Two Stray learning model was chosen because it can stimulate and encourage students to actively speak to convey ideas / ideas in discussion activities. The subjects of this study were students of class XI MIPA SMA Negeri 1 Muara Wahau. The data in this study were obtained through observation, interviews, student discussion skills tests, field notes, and documentation. Data were analyzed using qualitative descriptive techniques. The validity of the data was obtained through the validity (democratic, process, dialogic, results) of interview transcripts, observation sheets, discussion assessment sheets, and photos of activities. The results of the research obtained are the percentage of discussion skills indicators achievement has increased in each cycle. The students' average ability in discussing before the implementation of the action was categorized as lacking. However, after implementing the action for two cycles, the students' average ability in discussion was categorized as excellent. The results showed: (1) in the process, discussion learning has increased significantly. Prior to the implementation of the action, students were still not actively discussing and were not able to cooperate properly during the discussion. After the implementation of the action, students become active and able to work well together during discussions; (2) in product terms, students in discussions during the pre-action with an average score of 10, 63 and at the end of the implementation of the action, namely cycle II to 20.88. Students' ability in discussing has increased by 10.25